A Predictive Model of Nutrient Recovery from RAS Drum-Screen Effluent for Reuse in Aquaponics - Joseph Tetreault; Rachel L. Fogle; Ashly Ramos; Michael B. Timmons (Horticulturae, 2023)
Controlled environment agriculture (CEA) optimizes growth parameters for vegetable and aquaculture production and can be used to address growing global food insecurity. Recirculating aquaculture systems (RAS) generate a nutrient-dense effluent that may result in environmental pollution, but with treatment and integration with hydroponic vegetable production may be repurposed as a naturally derived nutrient solution. This work developed a preliminary model using the system feed rate to calculate a plant-essential nutrient discharge rate in RAS effluent. Loading rate equations were created to calculate the daily mass of nutrients entering the system through fish feed, and discharge rate equations were created to calculate the grams of each nutrient discharged in the effluent per kilogram of feed. Data from previous published work were used for validation. The loading-rate percentage discharged for nutrients present in the effluent was between 2.71% and 64.5%, with several nutrients being prominent pollutants and all being required for vegetable growth. This work provides the preliminary framework for calculating nutrient discharge rates, which can be used to mitigate pollution or develop more precise, naturally derived hydroponic nutrient solutions for a circular bioeconomy in CEA.